2010
DOI: 10.3109/09513590.2010.487603
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual irregularity: a possible clinical marker of metabolic dysfunction in women with class III obesity

Abstract: The presence of IR in class III obese women can cause menstrual dysfunctions such as amenorrhoea or oligomenorrhoea even in the absence of hyperandrogenism, suggesting that IR plays an important role in the ovarian mechanisms involved in the menstrual cycle control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
1
10
1
Order By: Relevance
“…Thyroid function tests, FBS and serum lipid pro le in two groups had not signi cant difference but in group two HOMA -IR was signi cantly higher than group 1. They concluded that IR in morbid obese women can make menstrual irregularity even without elevated androgens [10]. But in our study in 82% of obese women with normal menstrual pattern and in 85.28% of obese women with abnormal menstrual pattern HOMA -IR was more than 2.5.…”
Section: Discussioncontrasting
confidence: 63%
“…Thyroid function tests, FBS and serum lipid pro le in two groups had not signi cant difference but in group two HOMA -IR was signi cantly higher than group 1. They concluded that IR in morbid obese women can make menstrual irregularity even without elevated androgens [10]. But in our study in 82% of obese women with normal menstrual pattern and in 85.28% of obese women with abnormal menstrual pattern HOMA -IR was more than 2.5.…”
Section: Discussioncontrasting
confidence: 63%
“…Total testosterone and the free androgen index (FAI) were not different between the two groups of women [7]. Another study found that, in morbidly obese women, individuals who had menstrual dysfunction had greater insulin and HOMA-IR values [8]. Again, total testosterone and dehydroepiandrostenedione sulfate did not differ between the two groups of women [8].…”
Section: Introductionmentioning
confidence: 94%
“…Determining the degree of menstrual cycle irregularity in adult women is a simple clinical parameter which is a valuable instrument to estimate the degree of metabolic and endocrine disorders (5, 6). Within this frame of reference (13), we determined whether and to what degree annual reports of menstrual cycles ≥42 days during ages 14–19 years would be associated with obesity and endocrinopathy at 25 years of age.…”
mentioning
confidence: 99%